A simple test for multivariate conditional symmetry - SU, Liangjun (Institutional Knowledge at Singapore Management University, 2006)
This paper proposes a simple consistent nonparametric test of multivariate conditional symmetry based on the principle of characteristic functions. The test statistic is shown to be asymptotically normal under the null and consistent against any conditional asymmetric distributions.